(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Abstract: The article examines the trends and prospects for the production of organic food in the agricultural sector in the Republic of Bulgaria in the short and long term, as well as the problems faced by producers of organic food and organic products in a national and pan-European perspective. The production of organic food in the agricultural sector of the Republic of Bulgaria lags significantly behind compared to other countries. It represents only 2.3% of the total agricultural production of the country. At the same time, the Republic of Bulgaria, both in terms of climate, soils, and the degree of preservation of natural ecosystems, is extremely favorable for the development of organic agriculture and production of organic food in the agricultural sector. By offering relatively healthier food products and by protecting the environment, the production of organic food in the agricultural sector works in the interests of consumers. The production of organic food and organic products aims to support the health of consumers and is beneficial to the entire society.